Marine Bioremediation in Indonesia : Die Before Blossom - Agung Dhamar Syakti (Omni-Akuatika, 2018)
This critical review highlighted the need to booster an application of the environment biotechnology in order to reduce petroleum hydrocarbons contamination in marine environment.  Marine bioremediation can be promisingly applied when the spills occurred. However, absence of policy support from Indonesian government to endorse the private actor’s liabilities when complying the rehabilitation action was no significance while academic research was still far from establishment of fundamental knowledge in marine bioremediation. Thus, if so, it very likely that bioremediation disciplines and application might “die before blossom” in a country that often confronted by the maritime risk contamination of petroleum hydrocarbons on their marine and coastal area.